Muscle Twitch Kinetics Are Dependent on Muscle Group, Disease State, and Age in Duchenne Muscular Dystrophy Mouse Models - Peczkowski, Kyra K.; Rastogi, Neha; Lowe, Jeovanna; Floyd, Kyle T.; Schultz, Eric J.; Karaze, Tallib; Davis, Jonathan P.; Rafael-Fortney, Jill A.; Janssen, Paul M. L. (Frontiers in Physiology, 2020)
Duchenne muscular dystrophy (DMD) is an X-linked disorder caused by the lack of functional dystrophin protein. In muscular dystrophy preclinical research, it is pertinent to analyze the force of the muscles affected by the disease to assess pathology and potential effectiveness of therapeutic interventions. Although muscles function at sub-maximal levels in vivo, maximal tetanic contractions are most commonly used to assess and report muscle function in muscular dystrophy studies. At submaximal activation, the kinetics of contraction and relaxation are heavily impacted by the kinetics of the single twitch. However, maximal tetanic force is often the main, if not sole, outcome measured in most studies, while contractile kinetics are rarely reported. To investigate the effect of muscle disease on twitch contraction kinetics, isolated diaphragm and extensor digitorum longus (EDL) muscles of 10-week, 20-week, “het” (dystrophin deficient and utrophin haplo-insufficient), and 52-week mdx (dystrophin deficient) mice were analyzed and compared to wild-type controls. We observed that twitch contractile kinetics are dependent on muscle type, age, and disease state. Specific findings include that diaphragm from wildtype mice has a greater time to 50% relaxation (RT50) than time to peak tension (TTP) compared to the het and mdx dystrophic models, where there is a similar TTP compared to RT50. Diaphragm twitch kinetics remain virtually unchanged with age, while the EDL from het and mdx mice initially has a greater RT50 than TTP, but the TTP increases with age. The difference between EDL contractile kinetics of dystrophic and wildtype mice is more prominent at young age. Differences in kinetics yielded greater statistical significance compared to previously published force measurements, thus, using kinetics as an outcome parameter could potentially allow for use of smaller experimental groups in future study designs. Although this study focused on DMD models, our findings may be applicable to other skeletal muscle conditions and diseases.